EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN ARTICULATE STORYLINE TERHADAP HASIL BELAJAR IPA SISWA KELAS VII SMP NEGERI 2 PANCA RIJANG - Rahma, Siti; Usman M.; Muhammad Takdir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of the use of Articulate Storyline learning media on the science learning outcomes of grade VII students of SMP Negeri 2 Panca Rijang. The research method used is quantitative with a deductive approach. This type of research is a quasi experimental with a one group pretestposttest design. This study did not use a control group and an experimental group, but compared the learning outcomes of students before and after being treated in the form of the use of Articulate Storyline learning media. The research sample consisted of students in grades VII.1 and VII.2 with a total of 42 people. The research instrument used was a multiple-choice test given before (pretest) and after (posttest) treatment. The results showed that the average pretest score was 44.76, while the average posttest score increased to 84.88. The results of the N-Gain analysis showed a value of 0.7431 with an average percentage of 74.33%, which is included in the high category. This shows an increase in student learning outcomes after the use of Articulate Storyline learning media. Thus, it can be concluded that the use of Articulate Storyline learning media has proven to be effective in improving the science learning outcomes of grade VII students of SMP Negeri 2 Panca Rijang. Keywords: Articulate Storyline, Learning Outcomes, Effectiveness, Learning Media.